Generating Multistructured Ultrasound via Bioinspired Metaskin Patterning for Low‐Threshold and Contactless Control of Living Organisms (Adv. Funct. Mater. 33/2022). (15th August 2022) - Li, Peng‐Qi; Li, Zong‐Lin; Zhou, Wei; Wang, Shengwu; Meng, Long; Peng, Yu‐Gui; Chen, Zhi; Zheng, Hairong; Zhu, Xue‐Feng
Abstract : Bioinspired Metaskin Patterning In article number 2203109, Long Meng, Hairong Zheng, Xue‐Feng Zhu, and co‐workers report a reconfigurable acoustic meta‐skin with selective superhydrophobic decoration on a metal surface, which can be utilized for generating different structured ultrasounds and have potential applications in biological low‐intensity ultrasound stimulation of living organisms for the study of behavioral response and contactless control.